Prarancangan Pabrik Ferrosulfate Heptahydrate dari Pickling Liquor dan Asam Sulfat Kapasitas 20.000 Ton/Tahun - Rachmayanti, Yunita, Emi Erawati, S.T., M.Eng, Kusmiyati, S.T., M.T., Ph.D (2017)
Ferrosulfate heptahydrate factory was established to meet the needs of ferrosulfate heptahydrate in the country and abroad. It is based on the availability of raw materials and the need ferrosulfate heptahydrate in several industrial sectors. Ferrosulfate heptahydrate factories with raw materials pickling liquor and sulfuric acid is planned to be established with a capacity of 20,000 tons per year. The process of making ferrosulfate heptahydrate reaction performed on Continuous Stir Tank Reactor (CSTR) at operating conditions 85oC and a pressure of 1 atm. Endothermic reaction, isothermal condition, and takes place in non-adiabatic. After the manufacturing process and then do the process of crystal formation takes place in cristalizer 40oC operating conditions. Then continue the process of purification by means of separation of crystals with his mother liquor. Raw material requirements to meet the target of the resulting product is a pickling liquor as much 5.614,0933 kg/h and sulfuric acid as 5.319,3309 kg/h. Utility requirements in each year in the form of process water needs as much 14.051,5446 kg/h, for cooling water as much as 2.699,5371 kg/ hr, steam providers as much 6.011,5055 kg/hr, 194,3944 kW much electricity, and fuel as much as 0,0977 m3/h. Ferrosulfate heptahydrate factory is planned to set up in the city of Gresik with a building area of 23,000 m2 and a land area of 32,000 m2 and is planned to operate for 330 days. The establishment of the plant would also have to consider the number of workers. Ferrosulfat heptahydrate factory will be established with a number of employees 174 people. The economic analysis shows the amount of Rp 434,091,880,960.77 fixed capital and working capital of Rp 310,408,238,499.35. While the gains before tax hit 30% of Rp 163,244,005,389.38 and profit after tax of Rp 114,270,803,772.57 exposed Percent Return on Investment (ROI) before tax 32.81% and after tax 22.97%. Pay Out Time (POT) before tax of 2.34 years and after tax to 3.03 years. Break Event Point (BEP) by 54.4% and Shut Down Point (SDP) of 38.02%. Thus, the plant planned ferrosulfate heptahydrate is feasible to set up.